Gene network disruptions and neurogenesis defects in the adult Ts1Cje mouse model of Down syndrome - Hewitt, Chelsee Ann; Ling, King Hwa; Merson, Tobias D.; Simpson, Ken M.; Ritchie, Matthew E.; King, Sarah L.; Pritchard, Melanie A.; Smyth, Gordon K.; Thomas, Tim; Scott, Hamish S.; Voss, Anne K. (Public Library of Science, 2010)
Background: Down syndrome (DS) individuals suffer mental retardation with further cognitive decline and early onset Alzheimer's disease.